A novel RHH family transcription factor aCcr1 and its viral homologs dictate cell cycle progression in archaea. Issue 4 (30th January 2023) - Yang, Yunfeng; Liu, Junfeng; Fu, Xiaofei; Zhou, Fan; Zhang, Shuo; Zhang, Xuemei; Huang, Qihong; Krupovic, Mart; She, Qunxin; Ni, Jinfeng; Shen, Yulong
Abstract: Cell cycle regulation is of paramount importance for all forms of life. Here, we report that a conserved and essential cell cycle-specific transcription factor (designated as aCcr1) and its viral homologs control cell division in Sulfolobales. We show that the transcription level of accr1 reaches peak during active cell division (D-phase) subsequent to the expression of CdvA, an archaea-specific cell division protein. Cells over-expressing the 58-aa-long RHH (ribbon-helix-helix) family cellular transcription factor as well as the homologs encoded by large spindle-shaped viruses Acidianus two-tailed virus (ATV) and Sulfolobus monocaudavirus 3 (SMV3) display significant growth retardation and cell division failure, manifesting as enlarged cells with multiple chromosomes. aCcr1 over-expression results in downregulation of 17 genes (>4-fold), including cdvA . A conserved motif, aCcr1-box, located between the TATA-binding box and the translation initiation site of 13 out of the 17 highly repressed genes, is critical for aCcr1 binding. The aCcr1-box is present in the promoters and 5′ UTRs of cdvA genes across Sulfolobales, suggesting that aCcr1-mediated cdvA repression is an evolutionarily conserved mechanism by which archaeal cells dictate cytokinesis progression, whereas their viruses take advantage of this mechanism to manipulate the host cell cycle.